Systematic Literature Review: Pengaruh Premi dan Investasi Terhadap Laba Perusahaan Asuransi Syariah - Rian Dani; Romadhon Romadhon; Anzu Elvia Zahara; Usdeldi Usdeldi (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
This study aims to map the effect of premiums and investments on the profits of Islamic insurance companies. In research using the Systematic Literature Review method, eight articles out of 200 matched the criteria, with search strings from 2018 to 2022. The results showed that (RQ1) the problems contained in research journals varied, namely differences in results from previous studies on Premiums, Investment Returns, and Profits, as well as the decline in profits of Islamic insurance companies. In the research conducted by Alifia Nur Afifah and Anniza Citra Prajasari (2022), there are problems of inconsistency with the results of the previous study on premiums and profitability. In a study conducted by Ridwan Tabe et al. (2018), there are problems with the decline in net profit of the Panin Dai-ichi Life Sharia insurance company. And research conducted by Nur Indah et al. (2021) showed there needs to be more consistency in previous research between premiums for profits and investment for gains. (RQ2) The research method that is often used is the quantitative method; this method is very relevant because quantitative research looks at the "Facts/Truth" that are in the research object out there, and the researcher must be neutral about whatever is found in the field and be impartial. Furthermore, the results of the research question (RQ3) Every year and even in 2022, some journals discuss the effect of premiums and investments on the profits of Islamic companies.